Leveraging Gamification (Quizizz) for Enhanced Reading Comprehension Outcomes: A Quasy Experimental Investigation at Junior High School - Nina Afrida; Melly Permata Sari; Shafrida Wati; Muslem (JADEs Journal of Academia in English Education, 2025)
This study examined the effectiveness of Quizizz, a gamified digital learning platform, in enhancing students’ reading comprehension of descriptive texts at Junior high school in Langsa. Utilizing a quasi-experimental design with pre-test and post-test, the study involved 47 ninth-grade students divided into experimental and control groups. Statistical analysis conducted with SPSS version 25 revealed a significant improvement in the experimental group's mean reading comprehension score from 48.88 in the pre-test to 64.42 in the post-test, with an average gain of 15.54, compared to the control group's smaller gain of 7.00 (pre-test mean = 46.67, post-test mean = 53.67). The independent t-test confirmed a statistically significant difference between the groups (p = 0.000 < 0.05). These results underscore that Quizizz not only improves reading comprehension outcomes but also cultivates a more engaging and student-centered instructional environment. It is recommended that educators integrate Quizizz as an innovative instructional tool to foster student engagement and optimize reading comprehension proficiency.